In silico identification of noncompetitive inhibitors targeting an uncharacterized allosteric site of falcipain-2 - Hernández González, Jorge Enrique [UNESP]; Salas-Sarduy, Emir; Hernández Alvarez, Lilian [UNESP]; Barreto Gomes, Diego Enry; Pascutti, Pedro Geraldo; Oostenbrink, Chris; Leite, Vitor B. P. [UNESP] (Springer Nature, 2021)
Falcipain-2 (FP-2) is a Plasmodium falciparum hemoglobinase widely targeted in the search for antimalarials. FP-2 can be allosterically modulated by various noncompetitive inhibitors that have been serendipitously identified. Moreover, the crystal structures of two inhibitors bound to an allosteric site, termed site 6, of the homolog enzyme human cathepsin K (hCatK) suggest that the equivalent region in FP-2 might play a similar role. Here, we conduct the rational identification of FP-2 inhibitors through virtual screenings (VS) of compounds into several pocket-like conformations of site 6, sampled during molecular dynamics (MD) simulations of the free enzyme. Two noncompetitive inhibitors, ZINC03225317 and ZINC72290660, were confirmed using in vitro enzymatic assays and their poses into site 6 led to calculated binding free energies matching the experimental ones. Our results provide strong evidence about the allosteric inhibition of FP-2 through binding of small molecules to site 6, thus opening the way toward the discovery of new inhibitors against this enzyme.
Keywords: Allostery; Falcipain-2; Molecular dynamics; Noncompetitive inhibitor; Virtual screening